Differences in the verbal fluency, working memory and executive functions in alcoholics: Short-term vs. long-term abstainers. (March 2017) - Nowakowska-Domagała, Katarzyna; Jabłkowska-Górecka, Karolina; Mokros, Łukasz; Koprowicz, Jacek; Pietras, Tadeusz
Abstract: The aim of the study was to assess differences in verbal fluency, working memory and executive functions in two subgroups of alcohol-dependent patients, those undergoing short-term abstinence (STA) and those undergoing long-term abstinence (LTA), and to compare the level of cognitive functions in patients after long-term abstinence with healthy subjects. The study group consisted of 106 alcohol-dependent patients (53 immediately after drinking at least 3 days and 53 after at least one-year abstinence). The control group comprised 53 subjects, whose age, sex and education levels matched those of the patients in the experimental group. The dependence intensity was assessed using SADD and MAST scales. The neuropsychological assessment was based on the FAS Test, Stroop Test and TMT A&B Test. The results obtained for alcohol-dependent patients revealed significant disturbances of cognitive functions. Such results indicate the presence of severe frontal cerebral cortex dysfunctions. Frontal cortex dysfunctions affecting the verbal fluency and working memory subsystems and the executive functions also persisted during long-term abstinence periods. No significant correlations between the duration of dependence, quantity of alcohol consumed and efficiency of the working memory and executive functions were observed in alcohol-dependent subjects after short-term or long-term abstinence. Highlights: The results indicate the presence of severe frontal cerebral cortex dysfunctions. Patients revealed impairment of working memory(WM) and executive functions (EF). Frontal cortex dysfunctions persist also during long-term abstinence periods. The duration of alcoholism did not correlate with WM and EF efficiency. No correlations between alcohol quantity and WM and EF efficiency were observed.